Physics of Arctic landfast sea ice and implications on the cryosphere: an overview - Mengxi, Zhai; Leppäranta, Matti; Cheng, Bin; Ruibo, Lei; Fanyi, Zhang (Polar Research Institute of China - PRIC, 2021)
Landfast sea ice (LFSI) is a critical component of the Arctic sea ice cover, and is changing as a result of Arctic amplification of climate change. Located in coastal areas, LFSI is of great significance to the physical and ecological systems of the Arctic shelf and in local indigenous communities. We present an overview of the physics of Arctic LFSI and the associated implications on the cryosphere. LFSI is kept in place by four fasten mechanisms. The evolution of LFSI is mostly determined by thermodynamic processes, and can therefore be used as an indicator of local climate change. We also present the dynamic processes that are active prior to the formation of LFSI, and those that are involved in LFSI freeze-up and breakup. Season length, thickness and extent of Arctic LFSI are decreasing and showing different trends in different seas, and therefore, causing environmental and climatic impacts. An improved coordination of Arctic LFSI observation is needed with a unified and systematic observation network supported by cooperation between scientists and indigenous communities, as well as a better application of remote sensing data to acquire detailed LFSI cryosphere physical parameters, hence revolving both its annual cycle and long-term changes. Integrated investigations combining in situ measurements, satellite remote sensing and numerical modeling are needed to improve our understanding of the physical mechanisms of LFSI seasonal changes and their impacts on the environment and climate.